India’s Greening Trend Seems to Slow Down. What Does Aerosol Have to Do with It? - Manoj Hari; Bhishma Tyagi (Land, 2022)
Multiple drivers perturb the terrestrial carbon cycle, which ultimately reshapes the fertilization of carbon dioxide (CO2) and reorientates the climate. One such driver is atmospheric aerosols, which cascade the ecosystem’s productivity in a large proportionality. Investigating this relation is non-conventional and limited across the globe. With the abundance of heterogenetic terrestrial ecosystems, India’s primary productivity has a large proportion of the global carbon balance. Under climate change stress, India’s unique spatial and climatological features perturb atmospheric aerosols from natural sources to anthropogenic sources. In light of that, this study utilizes the Carnegie–Ames Stanford Approach (CASA) model to elucidate the consequence by examining the potential effect of aerosol load on the ecosystem productivity (Net Primary Production; NPP) for various agroclimatic zones of India from 2001–2020. CASA reveals a negative decadal amplitude with an overall increase in the NPP trend. In contrast, aerosol loadings from MODIS highlight the increasing trend, with definite seasonal intensities. Employing the CASA model and earth observations, the study highlights the increase in NPP in forest-based ecosystems due to relatively lower aerosols and higher diffuse radiation. Critically, strong dampening of NPP was observed in the agroecological and sparse vegetation zones inferring that the aerosol loadings affect the primary productivity by affecting the photosynthesis of canopy architecture. Spatial sensitivity zones across different ecological regions result in a non-homogenous response because of different phenological and canopy architecture that is mediated by the radiation intensities. Based on the analysis, the study infers that AOD positively influences the canopy-scale photosynthesis by diffuse radiation, which promotes NPP but is less likely for the crop canopy ecosystems. Barring the limitations, enhancement of NPP in the forest ecosystems offset the demand for carbon sink in the agroecosystems. Findings from this study reveal that a more precise provenance of aerosol effects on carbon fluxes is required to understand the uncertainties in the terrestrial carbon cycle.